MENINGKATKAN KEMAMPUAN BERHITUNG MELALUI MEDIA KOTAK PINTAR PADA USIA 5-6 TAHUN DI PAUD MATAHARI PETUKANGAN UTARA - Arie Rijanti; Asiyah; Sri Nurlaily (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The purpose of this article is to improve numeracy skills through smart box media in children aged 5-6 years at PAUD Matahari. This learning media is interesting and fun so that children do not feel bored. This research uses the Classroom Action Research (PTK) method which is carried out with two cycles, each cycle consists of planning, implementation, observation, and reflection stages. The results of the study showed that the use of smart boxes could improve the numeracy ability of children aged 5-6 years of PAUD Matahari. The achievement of quantitative results in the pre-cycle is 43%, so the child's ability to count has not been seen, so the first cycle action is carried out with the quantitative result increasing by 73%, meaning that the child's numeracy ability has developed but still needs improvement. In the second cycle, there was a significant increase of 97%, meaning that the child's numeracy ability has been seen and developed very well because it has reached the previously set criteria of 75%.